Geronimo Stilton: The Journey Through Time #3 : The Race Against Time (HC) - Stilton, Geronimo (Journey Through Time, #3, 2016)
Geronimo Stilton travels back in time to the ice age, ancient Greece, and Renaissance Italy, where he experiences wild historical adventures.